Estimasi Simpanan Karbon Hutan di Resort Pengelolaan Hutan (RPH) Alue Geulima Tahura Pocut Meurah Intan Aceh Besar: Estimation of Forest Carbon Stocks in RPH Alue Geulima Tahura Pocut Meurah Intan, Aceh Besar - Subhan; Ilham Hanafi; Putri Rosalinda; Ali Muhammad Muslih; Durrah Hayati (Jurnal Sumberdaya Hayati, 2023)
Forests are natural resources that play an essential role in climate change mitigation. Rising earth temperatures are causing climate change, which is driven by an increase in greenhouse particles, one of which is carbon particles. Human actions generate carbon particles. The amount of carbon absorbed and stored is critical to understanding and serves as a measure of forest condition. The study’s goal is to determine the amount of carbon stored in the Alue Geulima forest in Tahura Pocut Meurah Intan. The Alue Geulima Forest is a representative conservation area with high biodiversity and forest cover. Nested plot methods (in metres): tree level (20 × 20); pole level (10 × 10) and sapling level (5 × 5). Placement of plots systematically (uniform spacing) and the initial plots were placed randomly. The number of plots is 25 plots, sampling of intensity 0.5% represents 200 ha of Alue Geulima forest. The results showed that the value of carbon stocks stored in various strata of stands (trees, poles and saplings) found in 25 measuring plots reached 3,483.76 tons or the average reached the highest in RPH Alue Geulima found at the tree level, namely 2,338.41 tons ha-1. The total carbon stock stored above ground level in the Alue Geulima Tahura PMI Aceh Besar RPH as a whole is 139.35 tons ha-1 with total carbon stocks per 200 ha Alue Geulima RPH forest area of 27,870.08 tons.